Emigration behavior and molting during the sea‐to‐land transition of terrestrial hermit crabs under laboratory conditions. Issue 4 (20th November 2015) - Hamasaki, Katsuyuki; Hatta, Sora; Ishikawa, Takuma; Yamashita, Shota; Dan, Shigeki; Kitada, Shuichi
Abstract: Terrestrial hermit crabs in the family Coenobitidae (genera Coenobita and Birgus ) must migrate onto land after completing a pelagic larval stage in the ocean. Better knowledge of emigration behavior would assist in the conservation and management of coenobitid populations by helping identify and protect the habitats they need to complete their life cycles. We cultured laboratory‐born individuals of five coenobitid species ( Coenobita cavipes, C. purpureus, C. rugosus, C. violascens, and Birgus latro ) from megalopae to early juveniles (first, second, and/or third crabs) in vessels containing seawater and a hard substrate, and analyzed their behavior and molting in conjunction with our published data for C. brevimanus . Our results confirm that the coenobitids migrated from sea to land at the megalopal stage. Megalopae and early juveniles tended to select shells based on their body size. Inland‐dwelling coenobitids, such as C. brevimanus, C. cavipes, and B. latro, had a longer duration from landing to first molt and had a prolonged first crab intermolt period compared with those of the beach‐dwelling coenobitids C. purpureus, C. rugosus, and C. violascens, probably because of the adaptive traits for migrating to inland habitats. Little burrowing behavior was observed by megalopae of B. latro, but they had a strong tendency to be cryptic under shelters. Additionally, megalopae and early juveniles of Coenobita spp. created and utilized burrows somewhat differently. Our results suggest that coenobitids require specific microhabitats for completing their early life stages in the wild. In particular, megalopae of B. latro may need structurally complex refuges to migrate from the sea.